Isokinetic strength profile of the rotator muscles of high-level table tennis players - Rose, C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The practice of high-level table tennis require high muscular strength in the shoulders and the intensity of the strokes associated with a lot of repetitions can lead to overload particular joints [1]. However, few studies have explored the isokinetic profile of the rotator muscles of the table tennis players. Our objective was to describe and compare isokinetic muscle profiles of the shoulders of high-level table tennis players by laterality and gender. METHODS: 8 male (22 ± 4.6 years old; 181 ± 3.9 cm, 71 ± 7 kg) and 4 female (23 ± 8.2 years old; 168 ± 7.2 cm, 59 ± 10 kg) of the Table Tennis French Team were enrolled in this cross-sectional study. A clinical examination and a bilateral shoulder isokinetic test were carried out for all the athletes of the Table Tennis French Team as part of the annual medical check-up. The muscle strength of the internal rotators (IR) and external rotators (ER) of the shoulder were measured on an isokinetic dynamometer (Biodex system 4, Biodex Medical Systems, New York, USA) in the concentric mode at 60°/s and 180°/s, and the eccentric mode at 60°/s. The conventional ratio (ER : IR at 60°/s concentric mode) and the mixed ratios (ER in the eccentric mode at 60°/s to IR in the concentric mode at 180°/s for the throwing movement ; IR in the eccentric mode at 60°/s to ER in the concentric mode at 180°/s for the arming movement) were also calculated. RESULTS: The statistical analysis of the data in males shows only difference between the dominant arm and the non-dominant arm on the internal rotators in the concentric mode at 180°/s (0.66 ± 0.16 vs. 0.55 ± 0.11, P = .008). No difference was found in females between the two shoulders in any mode for the IR and the ER peak torque. There was no significant difference between sides for each of the ratios, in males and females. CONCLUSION: The isokinetic profile of high-level table tennis players, men and women, appears to be symmetrical between the racket arm (considered as the dominant one) and the non-dominant arm, with the possible exception of the internal rotators peak force in a high velocity condition (concentric mode at 180°/s), which is higher on the dominant side in males. Thus, it would be interesting to research in our high-level table tennis players suffering from pathology of the shoulder, if there is an imbalance of the muscular profile of the dominant side compare to those results.